Cell surface engineering of Saccharomyces cerevisiae for simultaneous valorization of corn cob and cheese whey via ethanol production. (1st September 2021) - Cunha, Joana T.; Gomes, Daniel G.; Romaní, Aloia; Inokuma, Kentaro; Hasunuma, Tomohisa; Kondo, Akihiko; Domingues, Lucília
Graphical abstract: Highlights: Evaluation of industrial Saccharomyces cerevisiae for consolidated bioprocessing. Development of a lactose-consuming cellulolytic Saccharomyces cerevisiae. Cell-surface display of cellulases and β-galactosidase in a robust industrial strain. High ethanol titers from a mixture of corn cob (high loads) and cheese whey. Increased ethanol productivity and reduced costs in this multi-feedstock approach. Abstract: The viability of 2nd generation bioethanol processes is dependent on achieving high ethanol titers, which requires the use of high solid loadings that will negatively affect the fermentative microorganism besides increasing enzyme-associated costs. To solve this, and also problems of feedstock availability, lignocellulosic biomass can be mixed with dairy by-products to increase carbon content. In this study, industrial strains of Saccharomyces cerevisiae, with improved thermotolerance and stress resistance, were engineered for the cell surface display of cellulolytic enzymes and were evaluated in consolidated bioprocessing of cellulose. Additionally, β-galactosidase was also displayed to enable lactose consumption, resulting in high ethanol titers (>50 g/L) from the simultaneous use of cheese whey and pretreated corn cob as substrate. The multi-feedstock valorization approach together with this lactose-consuming cellulolytic yeast allowed the reduction on materials costs by 60% with a 2.5-fold increase in the annual ethanol production, therefore contributing to the establishment of economic viable ethanol processes.